2015
DOI: 10.1186/s13000-015-0380-3
|View full text |Cite
|
Sign up to set email alerts
|

Does overexpression of HER-2 correlate with clinicopathological characteristics and prognosis in colorectal cancer? Evidence from a meta-analysis

Abstract: BackgroundPrevious studies have been inconsistent with respect to the reported associations between human epidermal growth factor receptor (HER-2/neu) overexpression in colorectal cancer. The aims of this meta-analysis are to assess its correlation with clinicopathological characteristics and prognostic significance in colorectal cancer.MethodsEligible studies were searched in Pubmed, Embase and Web of Science databases. The inclusion criteria were studies that assessed the relationship between HER-2 expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…181 However, initial results indicate HER2 overexpression may be predictive of resistance to EGFR-targeting monoclonal antibodies. 178,182 For example, in a cohort of 97 patients with RAS/BRAF wild-type metastatic CRC, median PFS on first-line therapy without an EGFR inhibitor was similar regardless of HER2 status.…”
Section: The Role Of Kras Nras and Braf Statusmentioning
confidence: 99%
“…181 However, initial results indicate HER2 overexpression may be predictive of resistance to EGFR-targeting monoclonal antibodies. 178,182 For example, in a cohort of 97 patients with RAS/BRAF wild-type metastatic CRC, median PFS on first-line therapy without an EGFR inhibitor was similar regardless of HER2 status.…”
Section: The Role Of Kras Nras and Braf Statusmentioning
confidence: 99%
“…Several studies assessed HER2 status in CRC, with some authors reporting membranous erbB2 overexpression in 2%-11% and others reporting cytoplasmic overexpression in 47%-68% of cases[ 48 - 52 ]. However, it is currently acknowledged that the amplification of HER2 occurs in only 3% of CRC[ 53 ]. In accordance to this notion, a recent comprehensive genomic characterization of CRC revealed a recurrent amplicon at 17q21.1 in 4% of these tumors[ 54 ].…”
Section: Her2 Testing In the Digestive Systemmentioning
confidence: 99%
“…In addition, in the present study we were unable to examine whether the specimen type (i.e., biopsied vs. surgically resected) affects concordance. Fourth, Wu et al (25) reported the correlation between HER2 status and clinicopathological parameters through meta-analysis. Their meta-analysis included studies which used HER2 IHC as well as Western blot and fluorescence ISH, limiting the interpretation of the clinicopathological significance of HER2 IHC overexpression (25).…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, Wu et al (25) reported the correlation between HER2 status and clinicopathological parameters through meta-analysis. Their meta-analysis included studies which used HER2 IHC as well as Western blot and fluorescence ISH, limiting the interpretation of the clinicopathological significance of HER2 IHC overexpression (25). The current study on the other hand included eligible studies that used HER2 IHC and carried out meta-analysis and diagnostic test accuracy review of HER2 IHC as well as concordance analysis between HER2 IHC and ISH, unlike the meta-analysis by Wu (25).…”
Section: Discussionmentioning
confidence: 99%